2008
DOI: 10.1097/01.hcr.0000314208.40170.00
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training Compared With Other Rehabilitation Interventions in Chronic Obstructive Pulmonary Disease

Abstract: Performing a combination of IMT plus exercise may lead to significant improvements in inspiratory muscle strength and one outcome of exercise tolerance for individuals with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
4
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 26 publications
1
62
4
2
Order By: Relevance
“…From meta-analyses it is clear that IMT increases inspiratory muscle strength and endurance, and decreases dyspnoea. However, exercise performance and quality of life did not improve significantly [18,20,21]. The addition of IMT to a general exercise programme did not improve exercise performance [20].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…From meta-analyses it is clear that IMT increases inspiratory muscle strength and endurance, and decreases dyspnoea. However, exercise performance and quality of life did not improve significantly [18,20,21]. The addition of IMT to a general exercise programme did not improve exercise performance [20].…”
mentioning
confidence: 99%
“…However, exercise performance and quality of life did not improve significantly [18,20,21]. The addition of IMT to a general exercise programme did not improve exercise performance [20]. Furthermore, differences in effects of resistance and endurance training were never analysed, while patient characteristics relevant for favourable effects of IMT have not been identified so far.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…33 This conclusion, however, was refuted by several later systematic reviews. [8][9][10] For example, Geddes et al 8 accounted for studies with methodological differences by examining threshold and targeted trainers separately from inspiratory resistive trainers with no target, and concluded that normocapneic hyperventilation, targeted inspiratory resistive, or threshold IMT significantly increased inspiratory muscle strength and endurance compared to sham IMT (see Table 1). The conflicting messages from the literature may have contributed to the confusion among physiotherapists with respect to this intervention (see Table 1).…”
Section: Research-related Factorsmentioning
confidence: 99%
“…1 Studies from Australia, 2,3 England, 3 Sweden, 4 the United States, 5,6 and Canada 7 have shown that physical therapists have a positive attitude toward EBP, but this attitude does not always translate into practice. For example, a variety of studies [8][9][10] have provided evidence supporting the use of inspiratory muscle training (IMT) for some people with chronic obstructive pulmonary disease (COPD), such as those who are unable to participate fully in whole-body exercise training because of comorbid conditions or those who have intractable dyspnea despite whole-body exercise. However, a survey of Canadian acute-care hospitals and pulmonary rehabilitation programmes found that less than 5% of physiotherapists prescribe IMT for COPD rehabilitation.…”
Section: Introductionmentioning
confidence: 99%